Fetal Dilated Myocardiopathy – Case Report: Association with a heterozygous mutation in MYH7 gene - Lopes, Danielle Negri de Souza; Bueno, Fernanda Saraiva; Gomes, Marcia Cristina de Azevedo; Ramos, Sergio; Martins, Fernando Freitas; Serão, Cassio Luiz de Carvalho; Moreira, Maria Elisabeth Lopes; Lopes, José Maria de Andrade (Brazilian Journal of Case Reports, 2024)
We report a case of dilated myocardiopathy with ascites and cardiac dysfunction detected at 20 weeks’ gestation. Baby was born at 33 weeks and 6 days, weighing 2530g, delivered by cesarean section and admitted to NICU. Postnatal echocardiography confirmed biventricular severe dysfunction, need of ventilatory support, vasoactive drugs, and prostaglandins. He was investigated for metabolic, infectious, and viral diseases with no positive results. After 6 weeks, he was transferred to a transplant center. Exome sequence showed a heterozygous mutation in the MYH7 gene (OMIN-160760.0028).